¿Es acaso el bien común un conjunto de condiciones? - Castaño, Sergio Raul (2020)
The thesis that defines common good as a ?set of conditions? is quite common among authors and theories that consider themselves as classical. Nevertheless, this definition, in its two most common forms (as the set of necessary conditions for the development of human person and as the identification of political end with the promotion of particular goods and rights) collides with the classical concept of common good, and with the reality itself, because it subordinates society (better said: the common good) to its parts and gives rise to a whole range of ontological and practical aporia. The key to a correct answer to the problem is the distinction between the end ?qui?, ?quo? and ?cui? as presented in the work of Louis Lachance and among several authors of the Argentine school of natural law.